Comparison of PFA-100 testing and bleeding time for detecting platelet hypofunction and von Willebrand disease in clinical practice - Posan, Emoke; McBane, Robert D., II; Grill, Diane E.; Motsko, Cheri L.; Nichols, William L. (Thrombosis and Haemostasis, 2003)
The PFA-100 instrument (Platelet Function Analyzer, Dade Behring) has been reported to be superior to the bleeding time (BT) as a screening test of primary hemostasis. However evaluation of this device has been principally limited to selected populations.The study’s aim was to determine testing performance in clinical practice, by comparing the PFA-100 to the BT for the identification of von Willebrand disease (VWD) and intrinsic platelet hypofunction.From 1998-2000, PFA-100 closure time (CT) for epinephrine-collagen (EPI) and ADP-collagen (ADP) cartridges and modified Ivy BTs were performed on outpatients referred for testing for suspected or known hemorrhagic diathesis (n=346). Evaluation included assays of von Willebrand factor and platelet aggregometry in addition to platelet flow cytometry and electron microscopy when indicated. The normal distribution of PFA-100 CTs was determined using blood samples from 61 normal donors studied on 155 occasions.Results show that thirty-four patients met the diagnostic criteria for VWD and 31 patients were diagnosed with congenital or acquired intrinsic platelet hypofunction. The sensitivity of the PFA-100 for identification of VWD was significantly better (p<0.01) than the BT with similar specificity. In contrast, the PFA-100 was comparable, but not superior to the BT for detecting platelet hypofunction.We conclude that the PFA-100 performance compares favor-ably to the BT for the identification of intrinsic platelet hypofunction in clinical practice with superior sensitivity for detecting VWD.Therefore, the PFA-100 could replace the BT for purposes of screening for VWD and intrinsic platelet hypofunction. When clinical suspicion is strong, testing should be supplemented with assays of von Willebrand factor and platelet aggregometry.
Keywords: Bleeding time; PFA-100; platelet hypofunction; von Willebrand disease